Preparation Techniques Used to Make Single‐Unit Crowns: Findings from The National Dental Practice‐Based Research Network. Issue 9 (8th November 2018) - Minyé, Helena M.; Gilbert, Gregg H.; Litaker, Mark S.; Mungia, Rahma; Meyerowitz, Cyril; Louis, David R.; Slootsky, Alan; Gordan, Valeria V.; McCracken, Michael S.; ,
Abstract: Purpose: To: (1) determine which preparation techniques clinicians use in routine clinical practice for single‐unit crown restorations; (2) test whether certain practice, dentist, and patient characteristics are significantly associated with these techniques. Materials and Methods: Dentists in the National Dental Practice‐Based Research Network participated in a questionnaire regarding preparation techniques, dental equipment used for single‐unit crown preparations, scheduled chair time, occlusal clearance determination, location of finish lines, magnification during preparation, supplemental lighting, shade selection, use of intraoral photographs, and trimming dies. Survey responses were compared by dentist and practice characteristics using ANOVA. Results: Of the 2132 eligible dentists, 1777 (83%) responded to the survey. The top two margin configuration choices for single‐unit crown preparation for posterior crowns were chamfer/heavy chamfer (65%) and shoulder (23%). For anterior crowns, the most prevalent choices were the chamfer (54%) and the shoulder (37%) configurations. Regarding shade selection, a combination of dentist, assistant, and patient input was used to select anterior shades 59% of the time. Photographs are used to communicate shade selection with the laboratory in about half of esthetically demanding cases. The ideal finish line was located at the crest of gingival tissue for 49% of respondents; 29% preferred 1 mm below the crest; and 22% preferred the finish line above the crest of tissue. Average chair time scheduled for a crown preparation appointment was 76 ± 21 minutes. Practice and dentist characteristics were significantly associated with margin choice including practice type ( p < 0.001), region ( p < 0.001), and years since graduation ( p < 0.001). Conclusions: Network dentists prefer chamfer/heavy chamfer margin designs, followed by shoulder preparations. These choices were related to practice and dentist characteristics.